Liquid smoke and its applications for fisheries products - Diah Lestari Ayudiarti; Rodiah Nurbaya Sari (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2010)
Liquid smoke is a volatile compound that simultaneously evaporates from heat reactor throughpyrolization and condense in cooler. Liquid smoke was produced in several steps that arepyrolization, condensation and redistillation. Quality, composition and material in liquid smoke isinfluenced by wood type as raw material. The major component of liquid smoke are acid, fenolderivate and carbonil. Those components can be used as flavoring, coloring, antibacterial andantioxidant agents. Liquid smoke can be used as preservative because of its antibacterial andantioxidant activity. Fenol and acetic acid compounds in liquid smoke can inhibit bacterial growthsuch as Pseudomonas fluorescence, Bacillus subtilis, Escherichia coli and Staphylococcusaureus. Fenol also can be used as antioxidant by stabilizing the free radicals. Liquid smoke cangive specific flavor and better color in smoke products. Liquid smoke can be applicated in eel, fishor products diversification such as fish steak. Liquid smoke also can be used in agricultural andtimber industry.